2018
DOI: 10.4103/0366-6999.247211
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen Activator Inhibitor 1 as a Poor Prognostic Indicator in Resectable Pancreatic Ductal Adenocarcinoma

Abstract: Background:Plasminogen activator inhibitor 1 (PAI-1) was previously established to impact several phenotypes in many kinds of cancer, including pancreatic cancer. However, its prognostic significance in pancreatic ductal adenocarcinoma (PDAC) needs support of further evidence. This study was designed to address the issue.Methods:PAI-1 expression was detected by tissue microarray-based immunohistochemical staining in formalin-fixed paraffin-embedded specimens from 93 PDAC patients with surgical resection from S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
0
5
1
1
Order By: Relevance
“…A previous study demonstrated that SERPINE1 is significantly associated with survival in PDAC patients, which is not in accord with other reports . Based on the results of the survival analysis in the present study, expression of SERPINE1 is negatively related to the survival of PDAC patients.…”
Section: Discussioncontrasting
confidence: 96%
“…A previous study demonstrated that SERPINE1 is significantly associated with survival in PDAC patients, which is not in accord with other reports . Based on the results of the survival analysis in the present study, expression of SERPINE1 is negatively related to the survival of PDAC patients.…”
Section: Discussioncontrasting
confidence: 96%
“…PAI-1, encoded by SERPINE1, is a member of the serpin superfamily and is an essential inhibitor of tissue plasminogen activator and urokinase-type (uPA), activators of plasminogen; PAI-1 can also bind LRP1, a major endocytic receptor [21,22]. The role of PAI-1 in thrombosis is generally known, and elevated PAI-1 levels in tumor tissues correlate with poor prognosis in patients with certain cancers (e.g., esophageal cancer, head and neck squamous cell carcinoma, gastric adenocarcinoma, pancreatic ductal adenocarcinoma, and urothelial carcinoma) [23][24][25]. Our findings identified CAFs as an important source of PAI-1 in the ESCC microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, glioma patients displaying a high expression of Serpine1 in biopsies have been known to show shorter overall survival (53). In other tumors as well, such as hepatocellular carcinoma, pancreatic ductal adenocarcinoma, and cervical cancer, high Serpine1 expression has been associated with a poor clinical outcome (54)(55)(56).…”
Section: Discussionmentioning
confidence: 99%